The Sorcerer of Cobenzl and His Legacy: The Life of Baron Karl Ludwig von Reichenbach, His Work and Its Aftermath - Nahm, Michael (Journal of Scientific Exploration, 2012)
<!–[if gte mso 9]> 800x600 <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false DE X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Normale Tabelle"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; mso-bidi-font-family:"Times New Roman"; –> <!–[endif] –>Karl Ludwig von Reichenbach was a well-known and controversial personality in the 19th century. The controversies largely centered on his theories concerning a universal and all-permeating force he claimed to have discovered—the “Od.” In this article, I highlight important events in von Reichenbach’s life and his explorations into the frontiers of science. Subsequently, I present an overview on lines of experimentation that have addressed two of his propositions, namely (a) that the effects of Od can be directly detected by macroscopic movements of objects such as compass needles, and (b) that (electro-)magnets can be detected visually in the dark due to the emission of odlight. Keywords: Reichenbach—Od—magnet—compass—light—visual perception